Spectrum of Systemic Auto-Inflammatory Diseases in India: A Multi-Centric Experience - Suri, Deepti; Rawat, Amit; Jindal, Ankur Kumar; Vignesh, Pandiarajan; Gupta, Anju; Pilania, Rakesh Kumar; Joshi, Vibhu; Arora, Kanika; Kumrah, Rajni; Anjani, Gummadi; Aggarwal, Amita; Phadke, Shubha; et al. (Frontiers in Immunology, 2021)
Background: Systemic autoinflammatory diseases (SAID) are rare inherited disorders involving genes regulating innate immune signalling and are characterized by periodic or chronic multi-systemic inflammation. Objective: To describe spectrum of clinical, immunological, molecular features and outcomes of patients with SAID in India. Methods: Request to share data was sent to multiple centres in India that are involved in care and management of patients with Inborn Errors of Immunity. Six centres provided requisite data that were compiled and analysed. Results: Data on 107 patients with SAID were collated - of these, 29 patients were excluded due to unavailability of complete information. Twelve patients (15%) had type 1 interferonopathies, twenty-one (26%) had diseases affecting inflammasomes, thirty patients (41%) had non-inflammasome related conditions and fifteen patients (19%) had Periodic Fever, Aphthous Stomatitis, Pharyngitis, Adenitis (PFAPA). Type1 interferonopathies identified in the cohort included patients with Deficiency of Adenosine Deaminase 2 (DADA2) (6 patients; 5 families); STING-associated vasculopathy infantile-onset (SAVI) (3 patients, 1 family); Spondyloenchondro-dysplasia with Immune Dysregulation (SPENCD) (2 patients). Diseases affecting inflammasomes include Mevalonate Kinase Deficiency (8 patients); Cryopyrin-Associated Periodic Syndromes (CAPS) (7 patients); NLR Family, Pyrin domain-containing 12 (NLRP12) (2 patients); Familial Mediterranean fever (FMF) (2 patients); Autoinflammation and PLCG2-associated antibody deficiency and immune dysregulation (APLAID) (2 patients). TNF receptor-associated periodic syndrome (TRAPS) (3 patients); A20 haploinsufficiency (4 patients); Deficiency of Interleukin 1 Receptor Antagonist (DIRA) (2 patients) were categorized as non-inflammasome related conditions. There were significant delays in diagnosis Corticosteroids and other immunosuppressive agents were used for treatment as anti-IL-1 drugs and other biological agents were and still are not available in India. Eight (16.3%) patients had so far succumbed to their illness. Conclusions: This is the first nationwide cohort of patients with SAID from India. Clinical manifestations were diverse. Overlapping of clinical features with other relatively common rheumatological disorders often resulted in delays in diagnosis. More nationwide efforts are needed to enhance awareness of SAID among health care professionals and there is an urgent need to make targeted immunotherapies universally available.